2014
DOI: 10.3390/ijerph110909739
|View full text |Cite
|
Sign up to set email alerts
|

Patient Experienced Continuity of Care in the Psychiatric Healthcare System—A Study Including Immigrants, Refugees and Ethnic Danes

Abstract: Aim: The purpose of this study was to investigate continuity of care in the psychiatric healthcare system from the perspective of patients, including vulnerable groups such as immigrants and refugees. Method: The study is based on 19 narrative interviews conducted with 15 patients with diverse migration backgrounds (immigrants, descendents, refugees, and ethnic Danes). Patients were recruited from a community psychiatric centre situated in an area with a high proportion of immigrants and refugees. Data were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 54 publications
0
20
0
3
Order By: Relevance
“…Over and above structural barriers to treatment such as availability and funding of qualified interpreters, or insurance coverage of psychotherapists, socio-cultural barriers are to be considered when treatment is enabled. Several studies showed that the cross-cultural setting might be a challenge to provide appropriate mental health care to refugees and asylum seekers for a variety of reasons such as stigma, taboo, trust issues, and a mismatch between Western concepts of diagnosis and treatment and the problems and needs perceived by refugees and asylum seekers [4,40,[65][66][67][68][69][70][71][72]. Moreover, the expression of the perceived problems, idioms of distress, or symptom expression of common mental disorders can vary substantially within and between cultural backgrounds and may decrease the accuracy of diagnostic appraisals and treatment outcome [73][74][75][76].…”
Section: Barriers To More Frequent Treatment Of Refugees and Asylum Smentioning
confidence: 99%
“…Over and above structural barriers to treatment such as availability and funding of qualified interpreters, or insurance coverage of psychotherapists, socio-cultural barriers are to be considered when treatment is enabled. Several studies showed that the cross-cultural setting might be a challenge to provide appropriate mental health care to refugees and asylum seekers for a variety of reasons such as stigma, taboo, trust issues, and a mismatch between Western concepts of diagnosis and treatment and the problems and needs perceived by refugees and asylum seekers [4,40,[65][66][67][68][69][70][71][72]. Moreover, the expression of the perceived problems, idioms of distress, or symptom expression of common mental disorders can vary substantially within and between cultural backgrounds and may decrease the accuracy of diagnostic appraisals and treatment outcome [73][74][75][76].…”
Section: Barriers To More Frequent Treatment Of Refugees and Asylum Smentioning
confidence: 99%
“…Closely related to flexibility of care is the responsiveness of care to changing service user needs and life circumstances (Durbin et al., ; Joyce et al., , ). However, this dimension is only represented in the literature surrounding a CoC scale called the ACSS‐MH (Alberta Continuity of Services Scale—Mental Health; Durbin et al., ), and in studies which use the conceptual framework for CoC based on factor analysis of this measure, such as Jensen, Johansen, Kastrup, Krasnik, and Norredam (). This suggests that further research is required to establish the generalizability of the component.…”
Section: Resultsmentioning
confidence: 99%
“…Significant overlap between components of the CoC concept is indicated by this review. For example, discharge planning may rightly be considered to be an important subtheme of experienced continuity since it impacts greatly on patient experience (Jensen et al., ; Poremski et al., ). However, discharge planning may also be considered to be a subcategory of cross‐boundary continuity (Sweeney et al., ; Uijen et al., ; Ware et al., ), since it relates to the effective coordination of care across service boundaries.…”
Section: Discussionmentioning
confidence: 99%
“…These findings support previous research, mostly about refugees, which indicates that transition to mainstream primary care is a difficult process. 6,[9][10][11][12][13][14][15] Patients' reluctance to transition has previously been attributed to a lack of clarity and coordination in the process, and a lack of available GPs.…”
Section: Discussionmentioning
confidence: 99%
“…6 The transition is often complicated by a lack of coordination between specialised and mainstream services 9 , reluctance among patients to transition 10 , difficulties in medical record transfer 11 , and the vulnerability of patients from a refugee background.…”
Section: Transitions In Carementioning
confidence: 99%